Ionic liquid-cellulose composite gel electrolyte as well as preparation method and application thereof
By using ionic liquid-cellulose composite gel electrolyte in lithium-ion batteries, the corrosion and compatibility problems of existing gel electrolytes during circulation are solved, and electrolytes with high ionic conductivity and mechanical strength are achieved, which improves the cycle stability and safety performance of the battery.
Patent Information
- Application Number
- CN202411769161.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
Existing gel electrolytes may corrode the polymer during long cycles, affecting the circulation and safety performance of the battery. At the same time, they are poorly compatible with lithium sheets, resulting in uneven lithium deposition and increasing the growth risk of lithium dendrites.
An ionic liquid-cellulose composite gel electrolyte is used, which connects the ionic liquid to allyl cellulose through covalent bonds and forms a network structure through a crosslinking agent to improve the mechanical strength and ionic conductivity of the electrolyte.
The gel electrolyte is achieved with high ionic conductivity, high mechanical strength and good thermal stability, reducing the uneven lithium deposition caused by polarization, and improving the cycle stability and safety performance of the battery.
Smart Images

Figure CN119613623A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to an ionic liquid-cellulose composite gel electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion battery is a high-capacity secondary battery with the advantages of high energy density, no memory effect, and green environmental protection. It has been widely used in many fields such as electric vehicles, consumer electronics, and aerospace. At present, the energy density of graphite materials commonly used in lithium-ion battery negative electrodes is low, which is difficult to meet the needs of high-power electric equipment. It is urgent to develop a new generation of negative electrode materials. Lithium metal has the advantages of low density, high theoretical capacity (3860mAh / g), and low redox potential. It is an irreplaceable negative electrode material for lithium batteries and has a very broad application prospect. However, lithium metal negative electrodes will inevitably form lithium dendrites during the battery charging and discharging process, and excessive growth of lithium dendrites will pierce the diaphragm and cause battery short circuit, which will eventually lead to dangerous situations such as fire and explosion. In response to this safety hazard, replacing liquid with solid (using solid electrolyte instead of liquid electrolyte) is an effective solution, but the ionic conductivity of solid electrolytes is generally low, which is not conducive to the improvement of battery cycle performance.
[0003] Gel electrolyte is a semi-solid electrolyte that combines the advantages of liquid electrolyte and solid electrolyte, and has both high ionic conductivity and high mechanical strength. However, in the long-term circulation process of existing gel electrolytes, the electrolyte may slightly corrode the polymer electrolyte, thereby changing the morphology of the electrolyte and affecting its mechanical properties, which will ultimately have a significant impact on the cycle performance and safety performance of the battery. In addition, the existing gel electrolyte also has the problem of poor compatibility with lithium sheets, which will cause uneven lithium deposition during the charging process of the battery, thereby aggravating the growth of lithium dendrites. In summary, the existing gel electrolytes are still difficult to fully meet the requirements of practical applications and need to be further improved.
[0004] Therefore, it is of great significance to develop a gel electrolyte with high ionic conductivity, high mechanical strength, good thermal stability and less polarization phenomenon. Summary of the invention
[0005] The purpose of the present invention is to provide an ionic liquid-cellulose composite gel electrolyte and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] An ionic liquid-cellulose composite gel electrolyte comprises allyl cellulose, ionic liquid and a crosslinking agent; the ionic liquid is connected to the allyl cellulose via a covalent bond; the crosslinking agent connects the allyl cellulose into a network structure via a covalent bond.
[0008] Preferably, the mass ratio of the allyl cellulose to the ionic liquid is 1:0.25-1.50.
[0009] Preferably, the mass ratio of the allyl cellulose to the cross-linking agent is 1:0.15-0.30.
[0010] Preferably, the degree of substitution of the allyl cellulose is 0.5 to 3.0.
[0011] Preferably, the ionic liquid is at least one of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide and N-[(2-methacryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide.
[0012] Preferably, the cross-linking agent is at least one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
[0013] Preferably, the number average molecular weight of the polyethylene glycol diacrylate is 400 g / mol to 1200 g / mol.
[0014] Preferably, the number average molecular weight of the polyethylene glycol dimethacrylate is 500 g / mol to 1500 g / mol.
[0015] A method for preparing the ionic liquid-cellulose composite gel electrolyte as described above comprises the following steps: dissolving allyl cellulose, ionic liquid, crosslinking agent and photoinitiator in an organic solvent, injecting into a mold for light crosslinking, and then purifying and drying the product to obtain the ionic liquid-cellulose composite gel electrolyte.
[0016] Preferably, the photoinitiator is at least one of benzoin dimethyl ether, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, and 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide.
[0017] Preferably, the organic solvent is at least one of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0018] Preferably, the light cross-linking is carried out under ultraviolet light irradiation, and the cross-linking time is 1 hour to 2 hours.
[0019] Preferably, the light cross-linking is carried out at room temperature (25°C±5°C).
[0020] Preferably, the product purification comprises the following operations: firstly soaking the product in ether for 5 to 10 minutes, then soaking it in tetrahydrofuran for 20 to 40 minutes, and then washing it with tetrahydrofuran for multiple times.
[0021] A lithium metal battery comprises the above-mentioned ionic liquid-cellulose composite gel electrolyte.
[0022] The beneficial effects of the present invention are as follows: the ionic liquid-cellulose composite gel electrolyte of the present invention has the advantages of high ionic conductivity, high mechanical strength, good thermal stability, less polarization phenomenon, etc., and its preparation method is simple to operate, mild reaction conditions, low raw material cost, and is suitable for large-scale industrial production and application.
[0023] Specifically:
[0024] 1) The ionic liquid-cellulose composite gel electrolyte of the present invention uses cellulose as a matrix, and the hydroxyl groups rich in cellulose can form hydrogen bonds, thereby providing the electrolyte with higher mechanical strength and support;
[0025] 2) The present invention grafts the ionic liquid onto allyl cellulose so that the ionic liquid and the allyl cellulose are connected in the form of a covalent bond, thereby fixing the cations in the ionic liquid, while the anions in the ionic liquid can move freely. The presence of the ionic liquid can stabilize the SEI layer and reduce the uneven lithium deposition caused by the polarization phenomenon;
[0026] 3) The present invention introduces a large number of EO segments into the electrolyte system through a cross-linking agent, and lithium ions can be transmitted through the EO segments, which promotes the transmission and movement of lithium ions, thereby effectively improving the ionic conductivity of the electrolyte system;
[0027] 4) The lithium symmetrical battery assembled with the ionic liquid-cellulose composite gel electrolyte of the present invention has good interface stability, and the assembled lithium iron phosphate battery has large specific capacity, excellent cycle stability and high coulombic efficiency;
[0028] 5) The reaction conditions of the synthesis process of the ionic liquid-cellulose composite gel electrolyte of the present invention are mild, and the light initiation reduces the energy consumption, while the use cost of cellulose is low and environmentally friendly, and it is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the Fourier transform infrared spectrum of the ionic liquid-cellulose composite gel electrolyte in Example 1.
[0030] Figure 2The stress-strain relationship curves of the ionic liquid-cellulose composite gel electrolytes in Examples 1 to 4 and the gel electrolyte in the comparative example.
[0031] Figure 3 AC impedance spectra of stainless steel symmetrical cells assembled with the ionic liquid-cellulose composite gel electrolytes in Examples 1 to 4 and the gel electrolyte in the comparative example.
[0032] Figure 4 LSV curves of batteries assembled with the ionic liquid-cellulose composite gel electrolytes in Examples 1 to 4 and the gel electrolyte in the comparative example.
[0033] Figure 5 The voltage-time relationship curve of the lithium symmetric battery assembled with the ionic liquid-cellulose composite gel electrolyte in Example 3 during the constant current cycle test.
[0034] Figure 6 The voltage-time relationship curve of the lithium symmetric battery assembled with the ionic liquid-cellulose composite gel electrolyte in Example 5 during the constant current cycle test.
[0035] Figure 7 The relationship curve between discharge capacity and cycle number during the charge and discharge test of the LFP battery assembled with the ionic liquid-cellulose composite gel electrolyte in Example 4. DETAILED DESCRIPTION
[0036] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0037] Embodiment 1:
[0038] An ionic liquid-cellulose composite gel electrolyte, the preparation method of which is as follows:
[0039] 100 mg of allyl cellulose (degree of substitution is 1.15) was stirred and dissolved in 2 g of N,N-dimethylformamide, and then 25 mg of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide (ionic liquid), 18.4 mg of polyethylene glycol diacrylate (number average molecular weight is 600 g / mol) and 15 mg of benzoin dimethyl ether were added and stirred evenly. The obtained solution was then injected into a polytetrafluoroethylene mold and allowed to stand at room temperature for 1.5 h under ultraviolet light (the solution becomes a gel), and then 20 mL of ether was added to soak for 6 min. After the ether was poured out, 20 mL of tetrahydrofuran was added to soak for 30 min. After the tetrahydrofuran was poured out, the product was washed twice with tetrahydrofuran and then placed in a blast drying oven at 55 °C for blast drying to obtain an ionic liquid-cellulose composite gel electrolyte (denoted as AC-P-1).
[0040] The synthesis reaction of the ionic liquid-cellulose composite gel electrolyte in this embodiment is as follows:
[0041]
[0042] The Fourier transform infrared spectrum of the ionic liquid-cellulose composite gel electrolyte (AC-P-1) in this example is as follows: Figure 1 shown.
[0043] Depend on Figure 1 It can be seen that at 1350cm -1 The asymmetric stretching vibration absorption peak of the ionic liquid anion O=S=O appears at 1220 cm -1 ~1170cm -1 The symmetric stretching vibration absorption peaks of the ionic liquid anion CF and O=S=O appeared at 1724cm -1 The stretching vibration absorption peak of C=O in polyethylene glycol diacrylate appeared at , indicating the successful introduction of the cross-linking agent.
[0044] Embodiment 2:
[0045] An ionic liquid-cellulose composite gel electrolyte, the preparation method of which is as follows:
[0046] 100 mg of allyl cellulose (degree of substitution is 1.15) was stirred and dissolved in 2 g of N,N-dimethylformamide, and then 50.7 mg of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, 18.4 mg of polyethylene glycol diacrylate (number average molecular weight is 600 g / mol) and 20 mg of benzoin dimethyl ether were added and stirred evenly. The obtained solution was then injected into a polytetrafluoroethylene mold and allowed to stand at room temperature for 1.5 h under ultraviolet light (the solution becomes a gel), and then 20 mL of ether was added to soak for 6 min. After the ether was poured out, 20 mL of tetrahydrofuran was added to soak for 30 min. After the tetrahydrofuran was poured out, the product was washed twice with tetrahydrofuran and then placed in a blast drying oven at 55 °C for blast drying to obtain an ionic liquid-cellulose composite gel electrolyte (denoted as AC-P-2).
[0047] Embodiment 3:
[0048] An ionic liquid-cellulose composite gel electrolyte, the preparation method of which is as follows:
[0049] 80 mg of allyl cellulose (substitution degree of 1.15) was stirred and dissolved in 2 g of N,N-dimethylformamide, and then 81 mg of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, 14.6 mg of polyethylene glycol diacrylate (number average molecular weight of 600 g / mol) and 20 mg of benzoin dimethyl ether were added and stirred evenly. The obtained solution was then injected into a polytetrafluoroethylene mold and allowed to stand at room temperature for 1.5 h under ultraviolet light (the solution turned into a gel), and then 20 mL of ether was added to soak for 6 min. After the ether was poured out, 20 mL of tetrahydrofuran was added to soak for 30 min. After the tetrahydrofuran was poured out, the product was washed twice with tetrahydrofuran and then placed in a blast drying oven at 55 °C for blast drying to obtain an ionic liquid-cellulose composite gel electrolyte (denoted as AC-P-3).
[0050] Embodiment 4:
[0051] An ionic liquid-cellulose composite gel electrolyte, the preparation method of which is as follows:
[0052] 80 mg of allyl cellulose (degree of substitution is 1.15) was stirred and dissolved in 2 g of N,N-dimethylformamide, and then 120 mg of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, 14.7 mg of polyethylene glycol diacrylate (number average molecular weight is 600 g / mol) and 24 mg of benzoin dimethyl ether were added and stirred evenly. The obtained solution was then injected into a polytetrafluoroethylene mold and allowed to stand at room temperature for 1.5 h under ultraviolet light (the solution becomes a gel), and then 20 mL of ether was added to soak for 6 min. After the ether was poured out, 20 mL of tetrahydrofuran was added to soak for 30 min. After the tetrahydrofuran was poured out, the product was washed twice with tetrahydrofuran and then placed in a blast drying oven at 55 °C for blast drying to obtain an ionic liquid-cellulose composite gel electrolyte (denoted as AC-P-4).
[0053] Embodiment 5:
[0054] An ionic liquid-cellulose composite gel electrolyte, the preparation method of which is as follows:
[0055] 100 mg of allyl cellulose (substitution degree 2.22; prepared using allyl glycidyl ether as etherifying agent) was stirred and dissolved in 2 g of N,N-dimethylformamide, and then 52.65 mg of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide, 53.48 mg of polyethylene glycol diacrylate (number average molecular weight 600 g / mol) and 30 mg of benzoin dimethyl ether were added and stirred evenly. The obtained solution was then injected into a polytetrafluoroethylene mold, and allowed to stand at room temperature for 1.5 h under ultraviolet light (the solution turned into a gel), and then 20 mL of ether was added to soak for 6 min, and then the ether was poured out and 20 mL of tetrahydrofuran was added to soak for 30 min, and then the tetrahydrofuran was poured out and the product was washed twice with tetrahydrofuran, and then placed in a blast drying oven at 55 ° C. Blast drying to obtain an ionic liquid-cellulose composite gel electrolyte (denoted as ACOH-P-1).
[0056] Comparative Example:
[0057] A gel electrolyte, the preparation method of which is as follows:
[0058] 100 mg of allyl cellulose (substitution degree is 1.15) was stirred and dissolved in 2 g of N, N-dimethylformamide, and then 18.4 mg of polyethylene glycol diacrylate (number average molecular weight is 600 g / mol) and 10 mg of benzoin dimethyl ether were added and stirred evenly. The obtained solution was then injected into a polytetrafluoroethylene mold and allowed to stand at room temperature for 1.5 h under ultraviolet light (the solution becomes a gel), and then 20 mL of ether was added and soaked for 6 min. After the ether was poured out, 20 mL of tetrahydrofuran was added and soaked for 30 min. After the tetrahydrofuran was poured out, the product was washed twice with tetrahydrofuran and then placed in a blast drying oven at 55 °C for blast drying to obtain a gel electrolyte (denoted as AC-P-0).
[0059] Performance Test:
[0060] 1) The ionic liquid-cellulose composite gel electrolytes in Examples 1 to 4 and the gel electrolytes in the comparative example were subjected to a tensile test (testing process: the gel electrolyte samples were cut into dumbbell-shaped strips with a length of 50 mm and a width of 4 mm, and then the tensile test was performed using a universal mechanical testing machine AG-X Plus at a tensile rate of 5 mm / min). The obtained stress-strain relationship curves are shown in FIG. Figure 2 shown.
[0061] Depend on Figure 2It can be seen that the tensile strength of the ionic liquid-cellulose composite gel electrolytes in Examples 1 to 4 is all above 20 MPa, showing a high level of mechanical properties, and as the content of the ionic liquid increases, the tensile strength of the ionic liquid-cellulose composite gel electrolyte shows a trend of first decreasing and then increasing. The reason is that the introduction of the ionic liquid increases the spacing between the cellulose molecular chains, and the hydrogen bonding effect is weakened, showing a lower tensile strength than the gel electrolyte in the comparative example. However, when the content of the ionic liquid reaches the level of Example 4, the tensile strength increases instead, because the ionic liquid forms a strong intermolecular force with the cellulose.
[0062] 2) The ionic liquid-cellulose composite gel electrolyte in Examples 1 to 4 and the gel electrolyte in the comparative example were immersed in a 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution (electrolyte, the solvent is composed of ethylene carbonate and diethyl carbonate in a volume ratio of 1:2), and then a stainless steel symmetrical battery was assembled in the order of a negative electrode shell, a spring, a stainless steel gasket, an electrolyte membrane, a stainless steel gasket and a positive electrode shell, and then an AC impedance test was performed (test process: the stainless steel symmetrical battery was connected to the positive and negative ends of the Coster CS310 electrochemical workstation, and the AC impedance option was selected for testing. The test frequency range was 10 5 Hz~0.1Hz, AC amplitude is 10mV, test temperature is 30℃), and then the ionic conductivity is calculated by the ionic conductivity calculation formula. The AC impedance spectrum is as follows Figure 3 shown.
[0063] The formula for calculating ionic conductivity is as follows: σ=d / (R b ×A), where σ is the ionic conductivity in S / cm, d is the thickness of the electrolyte membrane in cm, and R b is the body resistance of the electrolyte membrane, in Ω, and A is the contact area between the electrolyte membrane and the stainless steel gasket, in cm 2 .
[0064] Depend on Figure 3 It can be seen that (the intercept of the curve in the figure on the x-axis is the bulk impedance of the electrolyte membrane; the battery is disassembled, the actual thickness of the electrolyte membrane after liquid absorption and the actual contact area with the stainless steel gasket are measured, and then the ionic conductivity is calculated using the ionic conductivity calculation formula): as the content of the ionic liquid increases, the ionic conductivity of the ionic liquid-cellulose composite gel electrolyte shows a continuous upward trend. This is because the higher the content of the ionic liquid, the higher the liquid absorption rate of the electrolyte film, showing a trend of increasing ionic conductivity; the ionic conductivity of the ionic liquid-cellulose composite gel electrolyte in Example 4 is the highest, up to 1.67mS / cm 2 , which is more than 4 times that of the gel electrolyte in the comparative example, and generally shows higher ionic conductivity.
[0065] 3) The ionic liquid-cellulose composite gel electrolyte in Examples 1 to 4 and the gel electrolyte in the comparative example were immersed in a 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution (electrolyte, the solvent is composed of ethylene carbonate and diethyl carbonate in a volume ratio of 1:2), and then a battery with a stainless steel sheet (working electrode) and a lithium sheet (reference electrode) as two poles was assembled, and then a linear sweep voltammetry test was performed, with a scan range of 2.5V to 5.5V and a scan speed of 1mV / s. The obtained linear sweep voltammetry (LSV) curve is as shown in FIG. Figure 4 shown.
[0066] Depend on Figure 4 It can be seen that the oxidative decomposition voltage (the voltage when the current reaches 20μA) of the batteries assembled with the ionic liquid-cellulose composite gel electrolyte (introducing ionic liquid) in Examples 1 to 4 all reached above 4.5V, which is greater than the battery assembled with the gel electrolyte in the comparative example, indicating that the battery can operate in a wider voltage range, thereby allowing the design of a battery system with higher energy density.
[0067] 4) The ionic liquid-cellulose composite gel electrolyte in Example 3 and Example 5 was immersed in a 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution (electrolyte, the solvent was composed of ethylene carbonate and diethyl carbonate in a volume ratio of 1:2), and then a lithium symmetric battery was assembled, and then a constant current cycle test was performed at 25°C, and the current density was 0.3 mA / cm 2 The voltage-time relationship curve is as follows: Figure 5 and Figure 6 shown.
[0068] Depend on Figure 5 It can be seen that the lithium symmetric battery assembled with the ionic liquid-cellulose composite gel electrolyte in Example 3 has a high current density of 0.3 mA / cm 2 At a current density of , the voltage showed a very stable state and was maintained for more than 550 hours, indicating that the interface stability between the electrolyte and metallic lithium was good and the lithium deposition was uniform and stable.
[0069] Depend on Figure 6 It can be seen that the lithium symmetric battery assembled with the ionic liquid-cellulose composite gel electrolyte in Example 5 is 0.3 mA / cm 2 At a current density of , the voltage showed a very stable state and was maintained for more than 900 hours, indicating that the interface stability between the electrolyte and metallic lithium was good and the lithium deposition was uniform and stable.
[0070] After testing (same as above), the interfacial stability between the ionic liquid-cellulose composite gel electrolyte in Examples 1, 2 and 4 and metallic lithium is also good.
[0071] 5) The ionic liquid-cellulose composite gel electrolyte in Example 4 was immersed in a 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) solution (electrolyte, the solvent was composed of ethylene carbonate and diethyl carbonate in a volume ratio of 1:2), and then the LFP battery was assembled in the order of the negative electrode shell, the spring, the stainless steel gasket, the lithium sheet, the electrolyte membrane, the lithium iron phosphate positive electrode sheet and the positive electrode shell, and then the charge and discharge test was carried out at 25° C. with a rate of 1C. The obtained discharge capacity-cycle number relationship curve is as follows: Figure 7 shown.
[0072] Depend on Figure 7 It can be seen that the LFP battery assembled with the ionic liquid-cellulose composite gel electrolyte in Example 4 has an initial discharge capacity of 150 mAh / g at a rate of 1C, and after running for more than 500 cycles, the discharge capacity still remains above 110 mAh / g, showing very excellent cycle performance.
[0073] After testing (as above), the LFP batteries assembled with the ionic liquid-cellulose composite gel electrolyte in Examples 1 to 3 and 5 also have very excellent cycle performance.
[0074] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An ionic liquid-cellulose composite gel electrolyte, characterized in that: The composition comprises allyl cellulose, ionic liquid and cross-linking agent; the ionic liquid is connected with the allyl cellulose through covalent bonds; the cross-linking agent connects the allyl cellulose into a network structure through covalent bonds.
2. The ionic liquid-cellulose composite gel electrolyte according to claim 1, characterized in that: The mass ratio of the allyl cellulose to the ionic liquid is 1:0.25-1.
50.
3. The ionic liquid-cellulose composite gel electrolyte according to claim 1, characterized in that: The mass ratio of the allyl cellulose to the cross-linking agent is 1:0.15-0.
30.
4. The ionic liquid-cellulose composite gel electrolyte according to any one of claims 1 to 3, characterized in that: The substitution degree of the allyl cellulose is 0.5 to 3.
0.
5. The ionic liquid-cellulose composite gel electrolyte according to any one of claims 1 to 3, characterized in that: The ionic liquid is at least one of N-[(acryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide and N-[(2-methacryloyloxy)propyl]-N-methylpyrrolidine bis(trifluoromethylsulfonyl)imide.
6. The ionic liquid-cellulose composite gel electrolyte according to any one of claims 1 to 3, characterized in that: The cross-linking agent is at least one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
7. The ionic liquid-cellulose composite gel electrolyte according to claim 6, characterized in that: The number average molecular weight of the polyethylene glycol diacrylate is 400 g / mol to 1200 g / mol; the number average molecular weight of the polyethylene glycol dimethacrylate is 500 g / mol to 1500 g / mol.
8. A method for preparing the ionic liquid-cellulose composite gel electrolyte according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: dissolving allyl cellulose, ionic liquid, crosslinking agent and photoinitiator in an organic solvent, injecting into a mold for light crosslinking, and purifying and drying the product to obtain an ionic liquid-cellulose composite gel electrolyte.
9. The preparation method according to claim 8, characterized in that: The photoinitiator is at least one of benzoin dimethyl ether, 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, and 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide.
10. A lithium metal battery, characterized in that: The invention comprises the ionic liquid-cellulose composite gel electrolyte according to any one of claims 1 to 7.
Citation Information
Patent Citations
Gel type ionic liquid electrolyte for lithium ion battery as well as preparation method and application thereof
CN111653822A
Imidazole polyion liquid gel electrolyte and preparation method thereof
CN112185712A
Electrochemical energy storage polymer electrolyte and preparation method thereof
CN113745648A
Crosslinked cellulose-based gel polymer electrolyte and preparation method thereof
CN114725499A
Solid polymer electrolyte containing ionic liquid and preparation method thereof
CN115911541A